PERIOPERATIVE PROGRAMMED DEATH 1 EXPRESSION ON CD4+ T CELLS PREDICTS THE INCIDENCE OF POSTOPERATIVE INFECTIOUS COMPLICATIONS. Issue 4 (October 2015) - Kubo, Toru; Ono, Satoshi; Miyazaki, Hiromi; Saitoh, Daizoh; Yamamoto, Junji; Hase, Kazuo
ABSTRACT Introduction: Programmed death 1 (PD-1) has been reported to be an immunoinhibitory receptor expressed by chronically stimulated T cells after T-cell activation. The present study was designed to evaluate the relationship between perioperative PD-1 expression on CD4+ T cells and the incidence of postoperative infectious complications in patients undergoing gastroenterological surgery. Methods: One hundred one patients with gastroenterological disease were enrolled in this study. Blood samples were taken on the preoperative day (Pre) and the first postoperative day (POD1). We calculated the CD4+ T-cell count and the PD-1 expression on CD4+ T cells via flow cytometry. Results: Postoperative infectious complications occurred in 30 of the 101 patients. The CD4+ T-cell count was significantly lower in the patients who developed postoperative infectious complications at POD1 compared with the patients who did not. In addition, the PD-1 expression on CD4+ T cells was significantly higher at Pre or POD1 in the patients who developed postoperative infectious complications. The preoperative PD-1 expression on CD4+ T cells was found to be independently associated with postoperative infectious complications according to multivariate analysis. Conclusions: The perioperative CD4+ T-cell count or PD-1 expression on CD4+ T cells may be early predictive markers for the development of postoperative infectious complications.